A Prospective Comparative Study to Assess-Post Operative Analgesic Effect of Intraperitoneal Instillation of Bupivacaine with Dexmedetomidine to Bupivacaine with Tramadol in Patients Undergoing Laparoscopic Cholecystectomy (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: Tocompare post operativeanalgesic effect of intraperitoneal instillation of bupivacaine withdexmedetomidine, to bupivacaine with tramadol in patients undergoing laparoscopic cholecystectomy.Method: Sixty patients belonging to age group 20 to 50 years, from both sexes posted for laparoscopiccholecystectomy under general anesthesia were enrolled in our study. They were randomized in two groups,Group A and Group B with 30 patients each. ASA1 & ASA2 physical status were selected. A written andinformed consent was taken from all the patients. The group A received 35 ml of 0.25% Bupivacaine with50 mcgdexmedetomidine and Group B received 35 ml of 0.25% bupivacaine with 50 mg tramadol beforeremoval of trocar. The sites selected for instillation were hepato-diaphragmatic space (10ml), sub hepatic(10ml), on gall bladder bed (10ml) and near and above hepatoduodenal ligament (5ml), at the end of surgery.Intraoperative hemodynamic monitoring was done. Postoperative pain relief was assessed hourly for first6 hours by VASscore. Time to requirement of first dose of rescue analgesia was noted and this was theendpoint of this study, although the patients were monitored for 24 hours. Sideeffects like postoperativenausea, vomiting and respiratory depression were noted.Results: We noted that intraperitoneal instillation of bupivacaine with dexmedetomidine prolonged theduration of post operative analgesia compared to bupivacaine & tramadol combination. The requirementof first dose of rescue analgesic is delayed more inbupivacaine dexmedetomidine group as compared tobupivacaine tramadol group. Also the incidence of post operative nausea and vomiting was found to be lessin group Ai.e. bupivacaine dexmedetomidine group.Conclusion: From this study it can be concluded that the use of intraperitoneal instillation of bupivacainewith dexmedetomidine significantly reduces the requirement of post operative analgesics in patientsundergoing laparoscopic cholecystectomy with better compliance.
Keywords: Bupivacaine, Tramadol, Intraperitoneal Instillation, Laparoscopic cholecystectomy.